Experimental and Numerical Analysis of Critical Buckling Load of Honeycomb Sandwich Panels - Kaman, Mete Onur; Solmaz, Murat Yavuz; Turan, Kadir (Sage Publications Ltd, 2010)
The critical buckling loads for various core densities and materials of honeycomb composite panels are experimentally and numerically investigated in this study. The surface plates of honeycomb composite panels are of polyester/glass fiber composite. Polyester resin-impregnated paper or aluminum is used as the honeycomb core material. Honeycomb panels with different cell sizes, but approximately the same volume, are produced and the effect of the honeycomb core density on the critical buckling load is investigated by compression tests. The critical buckling load of paper core panels is determined to be higher than that of aluminum core panels. It is seen that the buckling strength of the specimens increases by the increase of core density. As the critical buckling load exceeds a certain limit, regional core cell buckling and core crushing are seen in aluminum core panels. In paper core panels, regional cracks are seen, in addition to these failures. The study also calculates the numeric buckling loads of the panels using the ANSYS finite element analysis program. The achieved experimental and numerical results are compared with each other and the results are provided in tables.
Keywords: honeycomb sandwich panel; buckling analysis; composite material; finite element method